Library Strategy in Improving Islamic Literacy Culture in MTs Miftahul Ulum Suren Jember - Aini, Mira Nur (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study aims to describe the library's strategy in improving Islamic literacy culture at MTs Miftahul Ulum Suren Jember. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, in-depth interviews, and documentation. The results of the study show that the strategies implemented include the formation of an Islamic Literacy Team in Schools, bringing in the Jember Library, collaborating with the publisher Erlangga, procurement of motivational words in the classroom, wall magazines, rewarding students who are active in reading, and providing reading corners in the school. This strategy has positive implications for increasing students' reading interest, literacy competence, and academic achievement. This study recommends the importance of sustainable innovation in Islamic literacy programs in schools.